Mechanical behavior of gypsum and cork based composite material - Vasconcelos, Graça (2013)
The main aim of this work is the mechanical characterization of a composite material resulting from the combination of three by-products coming from industry, namely, flue gas desulfurization (FGD) gypsum, granulated cork and textile fibers from tire recycling. The material is considered as a green material as the raw material are considered by-products and it is intended to be used as a building material for non-structural purposes in civil engineering construction. The mechanical characterization includes uniaxial compressive tests and bending tests for characterization of the fracture behavior. Additionally, ultrasonic pulse velocity is measured to evaluate its variation with time of curing.